The relation between gastric vitamin C concentrations, mucosal histology, and CagA seropositivity in the human stomach. Issue 3 (1st September 1998) - Zhang, Z W; Patchett, S E; Perrett, D; Katelaris, P H; Domizio, P; Farthing, M J G
Abstract : Background —Vitamin C may be protective against gastric cancer though infection with Helicobacter pylori is associated with a reduction in intragastric concentrations of vitamin C. Aims —To examine the effects of H pylori infection, gastric juice pH, the severity and extent of gastric inflammation, and CagA antibody status of the individual on gastric juice and mucosal vitamin C concentrations. Patients —One hundred and fifteen patients undergoing routine gastroscopy for investigation of dyspepsia. Methods —High performance liquid chromatography was used to determine vitamin C concentrations. CagA antibody was detected by western blot analysis. Results —Gastric juice ascorbic acid concentration was significantly lower in patients infected with H pylori compared with those uninfected (19.3 μmol/l (interquartile range (IQR) 10.7–44.5) versus 66.9 μmol/l (IQR 24.4–94.2), p=0.003). The reduction in gastric juice ascorbic acid concentration was inversely related to the severity of gastritis (p=0.01). CagA positive patients had significantly lower gastric juice ascorbic acid concentrations than CagA negative ones (14.8 μmol/l (IQR 7.9–52.2) versus 39 μmol/l (IQR 19.9–142.2), p=0.05). Decreased gastric juice dehydroascorbic acid concentrations were observed in patients with gastric atrophy and intestinal metaplasia. Mucosal ascorbic acid concentrations were also significantly lower in infected patients than uninfected patients (p=0.04). Conclusions —The reduction in gastric vitamin C concentrations is related to gastric juice pH, the severity and extent of gastritis, the presence of H pylori, and the CagA antibody status of the individual. These findings may have implications in H pylori associated carcinogenesis.